The Penetration of Mobile Technology and Its Implementation on Learning in Indonesian High School - Sulisworo, Dwi; Muqoyyanah, Muqoyyanah (Universitas Ahmad Dahlan, 2018)
The use of a smartphone as a mobile learning tool in schools is controversial. On the one hand, the teacher prohibits it because it would interfere with the learning process in the classroom; and on the other hand, the teacher saw a lot of potentials can be used from mobile technology. The goal of this study is to describe how the development of secondary schools in Indonesia can facilitate students through the use of mobile learning with the hope that it can be taken at the school level policies to strengthen the existing learning system so that students can achieve optimal learning competencies. This research used descriptive qualitative evaluations to make observations on the application of mobile learning in several secondary schools in several regions in Indonesia during 2015. The results of this study indicate that some of the schools that have implemented mobile learning have a tendency that mobile learning was not planned and structured as a school program; so that the advantages of mobile technology has not been effectively used. Two important things to solve this condition are the availability of government policy and improving teachers literacy in managing mobile learning application.